Finite element modelling of shear in hard turning - Kundrak, Janos; Szabo, G.; Varga, Gy. (НТУ "ХПИ", 2010)
The major problem of a choice of optimum finishing operation is solved at processing internal surfaces tempered of steels. Parameters by means of which it is obviously possible to carry out a choice of optimum operation turning or grindings are offered. The comparative analysis of efficiency of application of these operations has shown, that turning operation internal apertures at which the attitude of length to diameter does not exceed 1,1 is preferable.

The major problem of a choice of optimum finishing operation is solved at processing internal surfaces tempered of steels. Parameters by means of which it is obviously possible to carry out a choice of optimum operation turning or grindings are offered. The comparative analysis of efficiency of application of these operations has shown, that turning operation internal apertures at which the attitude of length to diameter does not exceed 1,1 is preferable.
Моделирование методом конечных элементов среза в токарной обработке
Keywords: steels; optimum operation turning; grinding; comparative analysis; закаленная сталь; точение; шлифование